2021
DOI: 10.3390/app11157018
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Planar Resonant Solutions for Glucose Concentration Sensing: A Systematic Review

Abstract: The measurement of glucose concentration finds interesting potential applications in both industry and biomedical contexts. Among the proposed solutions, the use of microwave planar resonant sensors has led to remarkable scientific activity during the last years. These sensors rely on the changes in the dielectric properties of the medium due to variations in the glucose concentration. These devices show electrical responses dependent on the surrounding dielectric properties, and therefore the changes in their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 152 publications
1
27
0
7
Order By: Relevance
“…The values of dielectric shift in Table 14 was calculated from the simulation graph in Figure 21 corresponding to the frequency shift observed when loading different samples. The sensitivity and normalized sensitivity [48] of the loaded samples is presented in Table 14. Sensitivity is computed as per Equation ( 6) and normalized sensitivity is com-puted as per Equation (7), where S N is the normalized sensitivity, ∆ f is the frequency shift, f r is the resonant frequency and ∆ε r is the shift in dielectric permittivity.…”
Section: Analysis Of Experimental Results and Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…The values of dielectric shift in Table 14 was calculated from the simulation graph in Figure 21 corresponding to the frequency shift observed when loading different samples. The sensitivity and normalized sensitivity [48] of the loaded samples is presented in Table 14. Sensitivity is computed as per Equation ( 6) and normalized sensitivity is com-puted as per Equation (7), where S N is the normalized sensitivity, ∆ f is the frequency shift, f r is the resonant frequency and ∆ε r is the shift in dielectric permittivity.…”
Section: Analysis Of Experimental Results and Comparisonsmentioning
confidence: 99%
“…When considering RF planar sensors, the sensitivity parameter may depend upon one or more parameters. From literature, we can find sensors based on resonant frequency, insertion/return loss, phase or quality factor (Q) [48]. The resonant frequency is an important parameter that has a direct relation with the sensitivity of the resonator structures [49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…Well-known methods are for example Raman spectroscopy, optical polarimetry (OP) or optical coherence tomography (OCT) [77]. The millimeter and microwave sensing and bioimpedance spectroscopy utilize the dielectric properties of glucose [28,77]. Both techniques are applied mostly over the skin.…”
Section: Electromagnetic Non-invasive Monitoringmentioning
confidence: 99%
“…These approaches can be classified according to the applied glucose sensing method. The primary sensing methods for NI methods are the electrochemical [24,25] and the electromagnetic-based methods [26][27][28]. In electrochemical NI glucose sensors, a probe of saliva [29], tear drop [30] or the exhaled breath [31] is analyzed.…”
mentioning
confidence: 99%
“…The general description of this type of sensor can be found in Ref. [21] and a good review on this topic can be found by Juan et al [31]. When materials are placed on top of the resonator, interaction between fields and samples will modify the resonant frequency f r and the corresponding quality factor Q.…”
Section: Introductionmentioning
confidence: 99%